Two loess landslide at the same hillslope triggered by the Mw 5.9 Minxian-Zhangxian earthquake in China (July 22, 2013): a comparative analysis of landslide mechanisms - Liu, Kun; Wang, Lanmin; Sun, Junjie; Xu, Shunhua; Lu, Yuxia; Tian, Wentong; Lu, Fucun (Frontiers in Earth Science, 2025)
Strong earthquakes and heavy rainfall are recognized as significant triggers of landslides, where the failure characteristics are intricately controlled by internal geological conditions of the slope. This study focuses on the investigation of two landslides triggered by the 2013 Minxian-Zhangye earthquake (Mw = 5.9, USGS). These landslides occurred on the Wamuchi slope, located approximately 22 km east of the epicenter in Minxian County, Gansu Province. Despite being less than 100 m apart, the two landslides exhibited significantly different flow sliding characteristics.The western landslide had a sliding distance of approximately 1.124 km, resulting in 12 fatalities, while the eastern landslide covered a distance of about 340 m.To further analyze the mechanisms of the two landslides and the reasons behind the differences in their flow sliding characteristics, we conducted field investigations and laboratory tests, including drilling, high-density electrical testing, unmanned aerial vehicle photography, and dynamic triaxial testing. A comparative analysis was performed on the landslide morphology, hydrogeological conditions, topography, and site-specific factors for both landslides.The results indicate that both landslides were triggered by a combination of seismic activity and rainfall. However, differing geological, hydrological, and topographical conditions, as well as site-specific influences, led to distinct mechanisms for each landslide, resulting in significant variations in their sliding characteristics.Understanding the initiation and movement mechanisms of such flowslides on slopes is crucial for effective landslide hazard analysis and mitigation strategies.